The Numerical Simulation Method of the Slot Crack Groups’ Effect Analysis for Solid Rocket Motor Grain - Tianpeng Li; Xiaonan Li; Zhaolong Xuan; Yu Guo (International Journal of Aerospace Engineering)
This study is aimed at the stability and effect of the crack groups in the solid rocket motor (SRM) grain when it was launched at normal temperature. Based on the nearly incompressible viscoelastic finite element method, several cracks were preset in a critical location along with the dangerous point of the back slot. The singular crack elements at the tips of crack groups were established to calculate the J-integral. With the position of the cracks, the J-integral of the various crack tips was, respectively, calculated to prejudge its stability and the group effect. Finally, the experimental measured critical J-integral JIC was compared with the numerical simulation result. The results showed that in the collinear crack groups, the enhancement effect of the main crack was caused by the nearest second crack, and the significant shielding effect of the main crack was occurred in the noncollinear crack groups. Moreover, the experimental result showed that the numerical method had high accuracy.